Displacement. - Galerie Unwahr, Berlin; Galerie Zderzak, Krakow (Berlin : Galerie Unwahr, 1992)
Baumgarten, Lothar ; De Cordier, Thierry ; Dimitrijevic, Braco ; Durham, Jimmie ; Fabre, Jan ; Kabakov, Ilya ; Kawamata, Tadashi ; Khakhar, Bhupen ; Kruk, Mariusz ; Meister, Ulrich ; Merz, Mario ; Yook, Keunbyung
Displacement, Galerie Unwahr, Berlin, 10.-24. Oktober 1992 / Galerie Zderzak, Krakow, 6. - 20. Dezember 1992
boek